Pelatihan peningkatan kompetensi guru SMK Satria dalam melaksanakan pembelajaran saintifik di Kota Jambi - Ekawarna, Ekawarna; Saharudin, Saharudin; Kusmana, Ade; Kristiyono, Santo (CV. Yudhistt Fateeh, 2023)
The urgent need for partner teachers (SMK Satria) at this time is